Seasonal Variation in Soil Moisture in Upland, Medium Land and Low Land Soils of Kanke (Ranchi) - Singh, R.A.; Deo, S.P. (Journal of Soil and Water Conservation, 2022)
Soil moisture forms one of the most important factors in successful crop production. Thus for more economical, safe, and best utilisation of soil and water for sustained production, a thorough understanding of the soil water relationship is a necessity. In the present investigation, therefore, the study of the seasonal soil moisture variations in the uplands medium lands, arid low lands of Kanke (Ranchi) was made for one year.